Catalysts of Employee Performance: Workload, Compensation, and Motivation: Mengungkap Pendorong Kinerja Karyawan: Beban Kerja, Kompensasi, dan Motivasi - Uswatun Nur Lailiya; Kumara Adji Kusuma (Academia Open, 2022)
This quantitative research study aimed to explore the impact of workload, compensation, and motivation on the performance of employees in the food industry. The research was conducted using a sample size of 100 employees from a cooking seasoning company in Sidoarjo, Indonesia. Data was collected through a questionnaire and analyzed using multiple linear regression in SPSS. The findings revealed that workload, compensation, and motivation had significant individual effects on employee performance. Furthermore, when considered together, these factors exhibited a collective influence on employee performance. This research provides valuable insights into enhancing employee performance within the context of the food industry, emphasizing the importance of managing workload, offering competitive compensation, and fostering motivation. The results have implications for both scholars and practitioners in terms of optimizing organizational performance and employee well-being. Highlights: The study examines the influence of workload, compensation, and motivation on employee performance. The research employs a quantitative approach and utilizes a sample size of 100 employees. Findings indicate that workload, compensation, and motivation individually and collectively impact employee performance. Keywords: employee performance, workload, compensation, motivation, quantitative research